The Impact of Public Spaces and Community Activities on the Economic Recovery of MSMEs in Cipayung, DKI Jakarta Province - Muthia Puspita Asri; Muhammad Findi A; Nora Herdiana Pandjaitan (Journal Research of Social Science, Economics, and Management, 2026)
The revitalization and development of public spaces during periods of social restriction, which later evolved into centers of social interaction in the post-pandemic era, play an important role in accelerating the economic recovery of Micro, Small, and Medium Enterprises (MSMEs) that were severely affected by the COVID-19 crisis. This study examines the contribution of public space reactivation to MSME economic recovery in the Cipayung District, DKI Jakarta Province. A quantitative descriptive approach was employed, involving 100 MSME respondents operating around ten major public spaces in the study area. Data were collected through a Likert-scale questionnaire and analyzed using SPSS to assess instrument validity and reliability, with a Cronbach’s Alpha value of 0.924 indicating high internal consistency. The Analytical Hierarchy Process (AHP) method was applied to identify priority factors and strategic alternatives for MSME recovery. The results show that the comfort of public spaces is the most influential factor supporting MSME economic recovery. Cleanliness, security, adequate basic facilities, and effective spatial design significantly increase visitor intensity and transaction activity. The second key factor is the diversity of community activities, including bazaars, cultural festivals, sports events, and social programs, which positively influence MSME turnover. Conversely, the number of public spaces has limited impact, highlighting that quality and activity intensity are more decisive than quantity. Respondents identified increased sales turnover, improved MSME competitiveness, and job creation as equally important recovery indicators. Based on AHP analysis, priority strategies include enhancing public space comfort and facilities, expanding community-based activities, strengthening MSME collaboration, improving government support.